Opinión pública y revolución liberal - Almuiña, Celso (Cuadernos de Historia Contemporánea, 2002)
Freedom of press in Spain dates back to the «Cádiz years» (1805-1813), hence the relevance of this period to the history of public opinion. In connection with the legislation it emerged from, three successive stages con be singled out as landmarks on the process: Bayonne granted chart (1808), Press Law (1810) and Constitution of 1812. Also, two distinct press models evolved throughout the War of Independence: the authoritarian, napoleonic paradigm and that of the patriot.